Developing a digital media literacy framework for Malaysian secondary school students : How literate is the young Malaysian population - SHANTHI, BALRAJ BABOO; AMBIGAPATHY, PANDIAN; MOHAMMED ZIN, NORDIN; SIAW WEE, CHEN; JOSEPH, RAMANAIR; KIRANJIT, KAUR; SOUBAKEAVATHI, RETHINASAMY; JING YI, LI (Suruhanjaya Komunikasi dan Multimedia Malaysia/Malaysian Communications and Multimedia Commission, 2020)
Young people spend a large portion of the awake hours on digital technologies ; but being digital natives does not mean that they are digital literates. With increasing urgency, media scholars, regulators and policy-makers have pointed to the need to create national standards of digital media assessment which would provide empirical bases for evaluating digital media literacy and digital participation of young people in Malaysia. This measure is important to facilitate interventions to ensure that we produce generations of young people who have good ideas, skills and values when approaching data-rich and complex digital media environments. A digital media literacy measurement framework with ten components and specific indicators under each component was created for use in a practical manner for research and policy impact. The components are : Operational, Information Navigation, Social, Mobile, Creative, Critical Understanding, Digital Citizenship, Safety, Regulation and Problem-Solving. The digital media literacy measurement framework was then tested and the findings suggest that on a scale of 1 to 5, the majority of participants in this study were on Level 3 – Fairly Competent, indicating the need for more educational endeavours in digital literacies among young people.